Strategi Pemerintah Kabupaten Solok Selatan dalam Melakukan Pengurangan Risiko Bencana Banjir - Wahib Assyahri; Febi Afni Milda; Iis Elfa Syafmaini; Oktaviaroza Oktaviaroza (Faculty of Social Science, Universitas Negeri Padang, 2022)
South Solok Regency is surrounded by hills and is fed by 13 rivers. With such natural landscapes, South Solok Regency is prone to flooding and the impact is felt by the community. Therefore, the government needs to take measures in the form of disaster risk reduction. But nature does disaster risk reduction, problems often occur which result in efforts to reduce disaster risk not maximally. So the purpose of this study is to describe the disaster risk reduction strategies implemented by the government and the factors that influence the government in reducing disaster risk. The research method used is a qualitative approach with descriptive techniques and analysis techniques using SWOT analysis. The results found are firstly that the district government has not optimally implemented disaster risk reduction due to insufficient budget and lack of facilities and infrastructure. Second, community participation is lacking in disaster risk reduction activities. The three communities do not protect the surrounding environment. So the government should use a strategy, first asking for financial assistance from the central and provincial governments. In addition, the business world should also provide grants to district governments to optimize disaster risk reduction activities and complete inadequate facilities and infrastructure. Second, approaching the community by visiting their homes so that the community can actively participate in disaster risk reduction. The three governments make regulations on protecting the environment.